Single-walled carbon nanotube networks for flexible and printed electronics - Zaumseil, Jana (Semiconductor science and technology, 2015)
Networks of single-walled carbon nanotubes (SWNTs) can be processed from solution and have excellent mechanical properties. They are highly flexible and stretchable. Depending on the type of nanotubes (semiconducting or metallic) they can be used as replacements for metal or transparent conductive oxide electrodes or as semiconducting layers for field-effect transistors (FETs) with high carrier mobilities. They are thus competitive alternatives to other solution-processable materials for flexible and printed electronics. This review introduces the basic properties of SWNTs, current methods for dispersion and separation of metallic and semiconducting SWNTs and techniques to deposit and pattern dense networks from dispersion. Recent examples of applications of carbon nanotubes as conductors and semiconductors in (opto-)electronic devices and integrated circuits will be discussed.